The Contribution Of Income Workes Woman Vegetable Trader To Family Income In The City Pontianak ( Case Study: Kemuning Market, Market Dahlia and Market Lotus)â€ - B01112055, Amalia Wihartati (Jurnal Pembangunan dan Pemerataan, 2016)
This Research aimed to find out and analyze the contribution of famale greengrocers’ income on the family income (Case Study at Kemuning Market, Dahlia Market an Teratai Market). A questionnare was used as the data collection tool. The technique for data analysis in this research the descriptive technique. The number of samples is in the research was 55 respondents.The research findings showed that contribution of the female greenggroces in the three markets was relatively high, i.e 80 percent and some were above 80 percent. This research also indicated that as much as 15 percent of the sellers at the Dahlia Market had informal education. Each seller at the three markets worked more than 8 hours a day, so that it can be said that the greengrocers at the three market viewed from the working hours had a high contribution. Most of the female greengrocers that became the respondents at kemuning market, dahlia market and teratai market were in the productive age (15-64 years old). The respondents were motivated to work increase income. In terms of the number of family members, most of the sellers at the three markets had 1-2 dependents. The respondents’ income was relatively high, so being a greengrocer was a reliable job to meet the family needs.Keywords: Education, Working Hours, Age, Motivation, Number Of Family Members Family, Mother’s Income.